2019
DOI: 10.1007/s00233-019-10022-3
|View full text |Cite
|
Sign up to set email alerts
|

On properties of square-free elements in commutative cancellative monoids

Abstract: We discuss various square-free factorizations in monoids in the context of: atomicity, ascending chain condition for principal ideals, decomposition, and a greatest common divisor property. Moreover, we obtain a full characterization of submonoids of factorial monoids in which all square-free elements of a submonoid are square-free in a monoid. We also present factorial properties implying that all atoms of a submonoid are square-free in a monoid.(1.1) A(M) ⊂ S(H).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…More information about Schreier and pre-Schreier domains we can see in many works, e.g. in [1], [5], [7], [14], [18], respectively. Lemma 2.13.…”
Section: First Note Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…More information about Schreier and pre-Schreier domains we can see in many works, e.g. in [1], [5], [7], [14], [18], respectively. Lemma 2.13.…”
Section: First Note Thatmentioning
confidence: 99%
“…In [18] Proposition 8.6 with Jȩdrzejewicz, Marciniak and Zieliński we received the characterization of square-free elements in composite A+XB[X], for A ⊂ B fields, i.e. Proposition 2.16.…”
Section: First Note Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…In section 4 we provide an encouraging overview of the initial theory of square-free factorizations for commutative cancellative monoids (in particular for Z), which was pioneered in the papers [4], [3], [6] and [7]. Let us recall (according to [2]) that by a commutative cancellative monoid we mean the semigroup H satisfying the law of contraction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another motivation is the article [10], where the properties of square-free ideals are described. Recall that the ideal I of a ring R is called square-free if for every x ∈ R, if x 2 ∈ I, then x ∈ I. Square-free ideals are a consequence of research on the theory of square-free factorizations, the results of which can be found in the papers [4][5][6][7]9,11] (in the case of radical factorizations) and in the author's doctoral thesis, which was highly appreciated by Professor Tadeusz Krasi ński from the University of Łódź in a review, motivating the author to further work on square-free factorizations.…”
Section: Introductionmentioning
confidence: 99%